Fundamentals of Management in the Health Care System (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
The Office of a Medical Organization requires a special approach due to the specificity of the product being produced to the market - medical services. Social significance of medical business dictates the use of special methods of management. While in modern companies, they argue about collective management, quality management and project management, most health organizations in Uzbekistan continue to work according to the Taylor model, adhering to tough subordination. It is necessary to note the importance of high-quality training of medical personnel and highly qualified management personnel, the activities of which will depend on the state of protection and health promotion of our country. Managing A Medical Organization Requires a Special Approach Due to the Specificity of the ProductBeing ReleasedTo The Market - a Medical Service. The Social Significance of the Medical Business Dictates The Use of Special Management Methods. While Modern Company Talk About Collective Management, Quality Management and Project Management, Most Healthcare Organizations in Uzbekistan Continue to Work According to the Taylor Model, Adhering to Strict Subordination.IT IS Necessary to Note The Importance of High-Quality Training of Medical Personnel and Highly Qualified Management Personnel, On Whose Activities The State of Protecting and Promoting The Health of the Population of Our Country Will Depend.